Spatial Autocorrelation of HIV Cases Based on Key and Special Populations in West Sumatra 2021–2024 - Diastanti, Yunita; Masrizal, Masrizal; Widoyo, Ratno (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
HIV cases continue to be a public health issue in West Sumatra Province, as seen from the increasing number of cases each year. Differences in regional characteristics are suspected to contribute to the pattern of HIV spread, so a spatial approach is needed to understand the variation in case distribution more deeply. This study uses an ecological study design by analyzing 19 districts/cities in West Sumatra during the period 2021-2024. The Global Moran’s I and LISA methods were applied to identify spatial autocorrelation patterns. The research results show that there are 7,260 HIV cases with a continuously increasing trend each year. Global spatial analysis shows a significant negative autocorrelation, indicating a dispersed distribution pattern, with a dominance of Low-High clusters in most regions. High spatial heterogeneity that is not concentrated in a single cluster was identified in West Sumatra province. Health policy interventions based on regional characteristics are needed to optimize resource allocation and future HIV prevention strategies.